Chemotherapy-induced heart failure of HER-2 Positive breast cancer: a scoping review (Research, Society and Development, 2022)
Breast cancer is the neoplasm that most affects women worldwide. Among the most established treatments for this pathology, and especially for the immunohistochemical subtype with overexpression of the Her-2 protein, is the use of chemotherapeutic agents, especially antineoplastic antibiotics and monoclonal drugs. However, these therapies can induce cardiotoxicity and heart failure events. The present study aims to evaluate aspects related to the development of heart failure resulting from chemotherapy treatment for Her-2 positive breast cancer. For this Scope Review, carried out through the PubMed and Science Direct platforms between 2020 and 2022, the descriptors chosen were ''Heart Failure'',''Breast Cancer'', ''Her-2'' and ''Ejection Fraction' ', associated with the boolean operator ''AND''. Inclusion criteria consisted of 1) clinical trials, controlled and randomized trials, reviews and meta-analyses; 2) studies on the induction of heart failure resulting from treatment for Her-2 positive breast cancer, 3) studies that evaluated the damage caused by cardiotoxicity, and 4) articles on the clinical management of heart failure. Exclusion criteria consisted of inadequacies to the topic, case reports and studies with animals, in addition to texts outside the time limit. It was observed that heart failure after the use of chemotherapy acted as a predictor of severe morbidity and mortality. Adverse events resulting from the use of antineoplastic drugs for Her-2 positive breast cancer ranged from a drop in ejection fraction to sudden death. The discontinuation of these drugs still remains a topic to be elucidated, as well as the application of cardioprotection strategies.